Stages of motor development in children with cyanotic congenital heart defects after surgical treatment - V.Yu. Martyniuk; N.M. Rudenko; O.V. Stohova; H.M. Fedushka (Zaslavsky O.Yu., 2024)
Background. The article deals with the actual problem of pediatric neurology, pediatric cardiology, and pediatric cardiac surgery, in particular, the peculiarities of neurodevelopment in children with congenital heart defects (CHD). The purpose is to conduct a study of stages of stato-motor development (SMD) in patients with cyanotic congenital heart defects after surgical treatment and to determine the influence of pathogenic factors on neurodevelopmental delay. Materials and methods. Thirty-five patients with cyanotic CHD underwent examination and surgical treatment at the Center for Pediatric Cardiology and Cardiac Surgery of the Ministry of Health of Ukraine: 20 children - with transposition of the great vessels (TGV) and 15 children - with tetralogy of Fallot (TOF). The control group consisted of 35 healthy patients whose motor development corresponded to their age. Gestational age, body weight at birth, Apgar score, saturation, and duration of artificial blood circulation during surgical treatment for CHD were considered. Assessment of motor development was carried out with the help of the following scales: Munich Functional Developmental Diagnosis (G.J. Köhler, H.D. Egelkraut) and section 2 of the Hammersmith Infant Neurological Examination. Data were processed using the software Microsoft Excel version 16.0.12527.21236. Results. The gestational age of the studied group of patients with cyanotic CHD was 38 weeks, body weight - 3,500 g, which corresponded to the control group. Patients of the first subgroup with TGV were diagnosed with lower saturation indicators (р = 0.0001), a lower 1-minute Apgar score (p = 0.028) and a longer duration of artificial blood circulation - 146.00 ± 29.03 (р = 0.043) compared to the second subgroup with TOF. SMD delay was diagnosed in 29 % of cases, namely 12 % with TGV and 17 % with TOF. The average period of sitting with delayed SMD was 8.4 ± 2.2 months (p = 0.002), walking - 18.4 ± 6.3 months (p = 0.0001). Subsequently, children with TGV continue to develop without a significant delay compared to the TOF subgroup. Conclusions. 1. Patients with cyanotic CHD are born at 38 weeks of gestation, with sufficient body weight without a significant difference depending on the type of CHD and compared to the control group of healthy children. The predominance of the male gender is typical in cyanotic CHD. However, children with transposition of the great vessels are characterized by a lower 1-minute Apgar score and lower indicators of saturation at birth compared to those with tetralogy of Fallot. 2. Based on the conducted study, a delay of SMD was found in 29 % of patients with cyanotic CHD, namely 17 % with TOF and 12 % with TGV. The average duration of sitting with delay was 8.4 ± 2.2 months and walking was 18.4 ± 6.3 months. 3. Surgical treatment was carried out according to the detected indications, for transposition of the great vessels on the first day and for tetralogy of Fallot at 8 months of life. No pathogenic influence of the duration of artificial blood circulation and aortic clamping during cardiosurgical treatment on SMD in children was found. An increase in the duration of artificial blood circulation was noted during arterial switch operation in children with TGV, but no significant difference was found in children with SMD delay. 4. Timely early surgical treatment of critical CHD - TGV on the first day after birth, a developed route for pregnant women, techniques of performing operations - ensure a better SMD of this subgroup in the future. In patients with TOF, taking into account the long period of hypoxia before the start of surgical correction, neuropsychiatric disorders of varying degrees are more often noted. The development of an individual rehabilitation program is provided for this category of children.